2021
DOI: 10.3390/ijerph18031159
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Method for Extraction and Determination of Residues of Selected Antimicrobials in Soil and Plant Samples Using HPLC-UV-MS/MS

Abstract: The residues of antimicrobials used in human and veterinary medicine are popular pollutants of anthropogenic origin. The main sources of introducing antimicrobials into the environment are sewage treatment plants and the agricultural industry. Antimicrobials in animal manure contaminate the surrounding soil as well as groundwater, and can be absorbed by plants. The presence of antimicrobials in food of plant origin may pose a threat to human health due to their high biological activity. As part of the research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…SLE-SPE extraction of five selected FCs from parsley root has already been studied by our research team [ 38 ]. In the present study, the SLE-SPE procedure was also used to extract 14 selected analytes, and the SLE step was modified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…SLE-SPE extraction of five selected FCs from parsley root has already been studied by our research team [ 38 ]. In the present study, the SLE-SPE procedure was also used to extract 14 selected analytes, and the SLE step was modified.…”
Section: Resultsmentioning
confidence: 99%
“…Reports have shown that the most common elution of analytes from HLB sorbent after passing the plant matrix extract is carried out under inert conditions-MeOH [6,9], although our study indicated that sequential elution with solvents of different pH gave a higher recovery of FCs. [38]. In the present study, the SLE-SPE procedure was also used to extract 14 selected analytes, and the SLE step was modified.…”
Section: Parsley Leaves-combining Sle-spe Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to past studies, mixing organic acids (including formic acid [39], phosphate [41], Na 2 EDTA-Mcllvaine [38,42]) with methanol [37] or ACN [43] is the most effective extraction solution with good recovery efficiency and has good reproducibility when analyzing multiple antibiotic residues in environmental matrices. Ferhi et al [34] demonstrated that ACN and citric acid-phosphate buffer can be used to efficiently extract eight antibiotics from the soil.…”
Section: Choice Of Extractantmentioning
confidence: 99%
“…However, AMs are not completely metabolized and a fraction between 17% and 90% is excreted unchanged in urine and feces, leading to notably widespread contamination of water and soil resources. AMs may enter agricultural fields mainly via the use of recycled water for irrigation due to the incomplete removal of these pharmaceuticals in wastewater treatment processes, and land application of sewage sludge, biosolids and manure as soil amendments or fertilizers instead of chemical fertilizers, which are restricted for organic vegetables [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%